Methodology for ranking the areas supplies for the forces of the National Guard of Ukraine in case of simultaneous occurrence of crises in several regions of the country - Аdаmchuk, М. М.; Babкоv, Yu. P.; Batsamut, V. М. (Honor and Law, 2019)
Based on the analysis methods of selection and prioritization, risk management elements of the theory of the technique of ranking areas of service and combat supplies for the forces of the National Guard of Ukraine in case of simultaneous occurrence of crises in several regions of the country.